2017
DOI: 10.1159/000484638
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Epidemiology of Transient Ischemic Attack in Dijon, France (2013–2015)

Abstract: Background: We aimed to evaluate the epidemiological features of transient ischemic attack (TIA). Methods: All TIAs were prospectively collected in Dijon, France, using a population-based registry (2013–2015). TIAs were considered the first-ever in patients who had no previous cerebrovascular events (CVEs); otherwise they were considered recurrent TIAs. Annual incidence (first-ever TIAs) and attack rates (first-ever and recurrent TIAs) were calculated. Results: Four hundred twenty TIAs were registered (255 fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This rise in men compared to women is particularly noticed in those under 65 years. The lower risk of TIA among women aged 55-64 years compared to men of same age is observed in other community-based studies undertaken during the 2000s [1][2][3][4][5][6][7][8][9][10] with available data ( Figure 2) and can be justified by the pre-menopausal gender protection effect conjugated with a more likely diagnosis of TIA mimics. A significant male/female odds ratio was previously reported by Warlow, 16 with high disparities in risk found among those aged 55-75 years, while in our study it is found in the youngest.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This rise in men compared to women is particularly noticed in those under 65 years. The lower risk of TIA among women aged 55-64 years compared to men of same age is observed in other community-based studies undertaken during the 2000s [1][2][3][4][5][6][7][8][9][10] with available data ( Figure 2) and can be justified by the pre-menopausal gender protection effect conjugated with a more likely diagnosis of TIA mimics. A significant male/female odds ratio was previously reported by Warlow, 16 with high disparities in risk found among those aged 55-75 years, while in our study it is found in the youngest.…”
Section: Discussionmentioning
confidence: 66%
“…Even with these restrictions, we decided to analyze changes over time, contrary to other communitybased studies describing separately a ''contemporary TIA profile,'' but with a substantially increase in incidence and different inclusion criteria. 9,10 Despite the contribution of better medical knowledge and population awareness to a predictable increase in incidence, improvements of primary and secondary prevention balanced this trend, contributing to a relative stability in incidence and stroke risk. The exhaustive data collection process including all transient focal symptoms/signs allowed us to include in both periods a wider range of cases mirroring the whole spectrum of disease, a probable source of differential bias in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, adjudication of potential TIA events in a community setting is particularly challenging because of TIA mimics and hospitalisation bias. 24,25 However, there are already a few population-based studies in which both stroke and TIA were ascertained and registered at the same time in the same study population, [26][27][28][29][30][31] thus providing support for the feasibility of such joint stroke and TIA incidence studies in different populations.…”
Section: Updated Standard Definitions Of Tia and Strokementioning
confidence: 99%
“…A previous study in the Dijon registry has shown that the rate of hospitalization among patients with a stroke in France is above 95% [48]. This rate is much lower among TIA patients and a recent epidemiological study, almost 20% of all cases were identified solely among one nonhospital source [49] . However, there is no well-organized out stroke clinic with easy access to imaging and cardiac investigations in our area, which may be in competition with the traditional hospital system.…”
Section: Discussionmentioning
confidence: 99%